Dyslipidemia Secondary to the Use of HAART in Adults: A Systematic Review - Oliveira, Diogo P. R.; Macêdo, Ana Paula Azevêdo; dos Santos Gonçalves, Mariane; Couto, Ricardo D. (Current Drug Research Reviews, 2022)
Background: HIV infection affects millions of people globally. Currently, although several drugs have brought an improvement in the quality and life expectancy of these individuals, they are accompanied by several adverse effects. Objective: To conduct a systematic review of studies examining the relationship between antiretroviral therapy (ART) uses and secondary dyslipidemia. Methods: The review followed the criteria defined by PRISMA. Only articles that completely evaluated the lipid profile were included, which consisted of total cholesterol (TC), triglycerides (TG), and LDL cholesterol (LDL-c), HDL cholesterol (HDL-c). Results: It was observed that the use of nucleoside and non-nucleoside reverse transcriptase inhibitor (NNRTI and NNRTI respectively) drugs and protease inhibitors are the most used in ART and are associated with changes in lipid profiles. The main changes observed were increases in TC, TG, and LDL-c in addition to a decrease in HDL-c. These patients had a higher risk of developing cardiovascular disease not only due to the use of therapy, but also due to the presence of other comorbidities evaluated in these studies, such as obesity, diabetes, and hypertension. The increase in age, the difference between genders, CD4 T-cell count, and viral load, were observed as risk factors for worsening dyslipidemia. Conclusion: According to the findings of this study, anti-HIV therapy is linked to dyslipidemia, which may or may not be the primary cause, and is frequently connected with a number of metabolic problems that can exacerbate the illness.
Keywords: dyslipidemia